The Decameron first day in perspective : volume one of the Lecturae Boccaccii - Weaver, Elissa B., 1940- (Toronto Italian studies., 2004)
Giovanni Boccaccio's Decameron is the best known and most read work in Italian literature next to Dante's Divine Comedy. In the tradition of Lectura Dantis, the practice of story-by-story critical readings of Dante's work, Elissa Weaver has collected essays from some of the most prominent American Boccaccio scholars to provide critical readings of the Decameron Proem, Introduction, and the ten stories that constitute the first of the ten 'days' of storytelling. The first of the twelve essays opens the volume with a consideration of the Proem, demonstrating the importance of Boccaccio's literary subtexts (Ovidian and Dantean) for understanding his poetics. The second essay, on the Introduction, discusses the title of the work and the framing tale. The remaining ten contributions treat in detail each story, examining the literary, ethical, and social concerns embodied in the short narratives and in the context provided by the comments and discussions of the story-tellers, and exploring the intertextual relations within the Decameron and with sources and analogues. This inaugural book in a new series of critical essays on the Decameron will provide an important guide to reading the complex series of narratives that constitute the opening of the Decameron and will serve as a guide to reading the entire work.